Our institutional experience with Spinal Epidural Abscess - Joulali, Y.; Lakhdar, F.; Benzagmout, M.; Chakour, K.; Chaoui, M. F. (Nepal Journal of Neuroscience, 2019)
Corrigendum The article published in Nepal Journal of Neurosciences 2019;16:16-19 by Joulali Youssef etal was mistakenly published with a wrong co-author. The corresponding author has submitted following authors as responsible for the article, Y. Joulali, F. Lakhdar, M. Benzagmout, K. Chakour and M.F. Chaoui. Bipin Chaurasia was added in error. Please cite this article as Joulali Y, Lakhdar F, Benzagmout M, Chakour K, Chaoui MF. Our institutional experience with Spinal Epidural Abscess. Nepal Journal of Neurosciences 2019 ; 16:16-19 in future citations. Abstract: Spinal epidural abscess is a rare pathology which is manifested by a classic triad of pain, fever and neurological deficit. In most cases, the clinical picture is incomplete which makes its diagnosis difficult. In this retrospective study, we report five cases of spinal epidural abscess treated in the neurosurgery department of Hassan II University Hospital of Fez. Four of our patients were admitted due to spinal cord compression, while one patient was admitted for isolated spinal syndrome without neurological deficit. Fever was present in all our patients, nevertheless no point of entry was identified in the initial assessment. MRI was performed on emergency basis in all of our patients which demonstrated an extra-dural hypo intensity on T1WI, hyper intensity on T2WI. It also showed lesions with peripheral enhancement after contrast with gadolinium. Four of our patients underwent surgical treatment which involved performing alaminectomy/laminotomy with drainage of the abscess, while one patient received medical treatment alone. The evolution was favorable in 4 of our patients while one patient died post operatively due to severe sepsis.